Sustainable chemical processing of flowing wastewater through microwave energy. (January 2022) - Siddique, Fizza; Mirzaei, Amir; Gonzalez-Cortes, Sergio; Slocombe, Daniel; Al-Megren, Hamid A.; Xiao, Tiancun; Rafiq, M.A.; Edwards, Peter P.
Abstract: Iron oxide nanostructured catalysts have emerged as potential candidates for efficient energy conversion and electrochemical energy storage devices. However, synthesis and design of nanomaterial plays a key role in its performance and efficiency. Herein, we describe a one-pot solution combustion synthesis (SCS) of α-Fe2 O3 with glycine as a fuel, and a subsequent reduction step to produce iron-containing catalysts (i.e., Fe3 O4, Fe–Fe3 O4, and Fe 0 ). The synthesized iron-based nanoparticles were investigated for methyl orange (MO) degradation through Microwave (MW) energy under continuous flow conditions. Fe–Fe3 O4 showed higher MO degradation efficiency than α-Fe2 O3, Fe3 O4 and Fe 0 at low absorbed MW power (i.e. 5–80 W). The enhanced degradation efficiency is associated to the combination of higher availability of electron density and higher heating effect under MW energy. Investigation of dielectric properties showed relative dielectric loss of Fe3 O4, Fe–Fe3 O4, and Fe 0 as 3847, 2010, and 1952, respectively. The calculated average local temperature by the comparative analysis of MW treatment with conventional thermal (CT) treatment showed a marked thermal effect of MW-initiated MO degradation. This work highlights the potential of microwave-driven water depollution under continuous-flow processing conditions and demonstrates the positive impact that earth-abundant Fe catalyst synthesized by green SCS method can have over the treatment of wastewater. Highlights: Microwaves and low oxidation state of Fe catalysts enhance methyl orange degradation. Reduction of iron oxide produces effective catalysts for flowing wastewater depollution. Average temperature of iron-based catalysts resulted superior than surface temperature. Solution combustion is an eco-friendly method for synthesizing iron oxide.